Adaptive Body Support System For Aircraft Seat - Tan, Chee Fai; Rauterberg, Matthias; Chen, Wei; Kher, Vee Kiat (Trans Tech Publications, 2013)
The development of new technology enables the comfort service becoming an important requirement in the air travel industry. Long haul air travel may cause different physiological and psychological discomfort of aircraft passenger. Most of the aircraft company treats the passenger comfort as a main priority for the user’s acceptance of their airline. In order to improve the aircraft passenger body comfort during long haul air travel, an adaptive body support system was developed and embedded in the economy class aircraft seat. In this paper, we describe the development of adaptive body support system.